2016
DOI: 10.1136/tobaccocontrol-2015-052844
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette sales to minors via the internet: how the story has changed in the wake of federal regulation

Abstract: Objective To assess how easily minors can purchase cigarettes online and online cigarette vendors’ compliance with federal age/ID verification and shipping regulations, North Carolina’s 2013 tobacco age verification law, and federal prohibitions on the sale of non-menthol flavoured cigarettes or those labelled or advertised as light’. Methods In early 2014, 10 minors aged 14–17 attempted to purchase cigarettes by credit card and electronic check from 68 popular internet vendors. Results Minors received cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 15 publications
(20 reference statements)
0
17
0
1
Order By: Relevance
“…Minors are easily able to purchase electronic cigarettes from the internet because of absent or weak age verification measures used by vendors. A recent study showed that minors successfully received deliveries of electronic cigarettes from 77% of purchase attempts and delivery companies never attempted to verify their age at delivery [101].…”
Section: Regulation Of Electronic Cigarettesmentioning
confidence: 99%
“…Minors are easily able to purchase electronic cigarettes from the internet because of absent or weak age verification measures used by vendors. A recent study showed that minors successfully received deliveries of electronic cigarettes from 77% of purchase attempts and delivery companies never attempted to verify their age at delivery [101].…”
Section: Regulation Of Electronic Cigarettesmentioning
confidence: 99%
“…El benceno se asocia a daños en la línea mieloide y linfoide de las células hematopoyéticas, aumentando el riesgo de desarrollar leucemia linfoide o mieloide agudas (60,61) . Recientes estudios asocian los casos de leucemia linfoblástica aguda en menores de 15 años con la exposición al tabaco, derivada de la compra ilegal de este producto, pese a las disposiciones legales que prohíben su venta a menores de 18 años (62)(63)(64) .…”
Section: Tabacounclassified
“…Internet vendors continue to promote tax free cigarette sales and the Act is ineffectively enforced. 43 A high level of credit card fraud associated with online tobacco purchase attempts may limit such sales. 43 Health harms of tobacco are aggravated by simultaneous alcohol use.…”
Section: Disadvantagesmentioning
confidence: 99%
“…43 A high level of credit card fraud associated with online tobacco purchase attempts may limit such sales. 43 Health harms of tobacco are aggravated by simultaneous alcohol use. 44 If both substances are sold at the same locations, dual use could increase.…”
Section: Disadvantagesmentioning
confidence: 99%